Corpora Techniques in Analyzing Jadid Literature: A Linguistic and Cultural Exploration - Dalieva, Madina (The Lingua Spectrum, 2025)
This article investigates the application of corpus-based techniques in the study of Jadid literature, focusing on textual patterns, semantic associations, and cultural implications. Jadid writers – champions of reform and enlightenment in Central Asia – used language innovatively to disseminate modernist ideas. By constructing specialized corpora of Jadid texts and employing computational tools such as frequency analysis, concordancing, and collocation analysis, researchers can unveil nuanced linguistic trends and cultural motifs. This paper outlines methodological considerations for corpus construction, discusses key findings from pilot studies, and evaluates challenges and future directions. Ultimately, this study highlights how corpus-based approaches can enrich literary criticism and facilitate interdisciplinary research on the Jadid movement.